Caregivers’ Burden and Financial Distress in Parents of Children with Cancer: A Descriptive Correlational Study - Alnaji, Maisaa; Alafafsheh, Ahmad; Farrayeh, Muna; Salameh, Saba; Al Mahameed, Yasmeen (Asian Pacific Journal of Cancer Nursing, 2026)
Background: Cancer and its treatment pose a challenge to the child and the caregiver. The lengthy treatment and the suffering of the child from the side effects are highly demanding on the side of the caregiver in terms of the physical, social, and financial aspects. This study aims to measure the caregivers’ burden and financial distress among parents of children with cancer. Materials and Methods: A cross-sectional study design using a convenience sample of 158 parents of children with cancer completed two surveys on caregivers’ burden and financial distress. Results: Parents of cancer experianced moderate finanicial distress, with most reported mild to modearte level of cargiver burden. This study highlights that caregivers of children with cancer experience a significant level of burden and financial distress that may affect them negatively and affect their role as caregivers. Early assessment of caregiver burden and faninical status is essential to improve treatment adherance and prevent adverse outcomes. Conclusion: The study shows significant financial and caregiver burden, highlighting the need for better support services.